Intraoperative Incidental Internal Carotid Artery Injury in Extended Endoscopic Endonasal Approaches—Causes, Prevention, and Management: A Technical Note - Manjul Muraleedharan; Arushi Kumar; Ravisankar Manogaran; Ashuthosh Kumar; Amit Kumar Keshri; Vivek Singh; Raj Kumar (Indian Journal of Neurosurgery)
In spite of good anatomical awareness, the position of internal carotid artery (ICA) can be tricky in an intraoperative setup with disease causing very significant distortion of anatomy and shift of carotid artery and its branches. A 45-year-old gentleman presented with complaints of left hemicranial headache and painless progressive vision loss in both eyes (left more than right) for 8 months. A probable clinico-radiological diagnosis of meningioma was reached. Intraoperatively, bleeding occurred from left side ICA, control of which was achieved using a long gauze piece used as conventional nasal pack with crushed muscle beneath the gauze piece along with abdominal fat, which was further reinforced with Surgicel. The parasellar ICA is the most common segment injured. Dehiscent or bulging canal of ICA, presence of pseudoaneurysm, attachment of sphenoid septae to the canal, displacement by the lesion, nonenlarged sella because of small size of lesion or vertically oriented lesions, and vessel wall abnormalities increase the risk of injury. It is very essential to have a preoperative discussion involving the skull base surgeons (neurosurgeons and otorhinolaryngologists), neuroradiologists, and neuroanesthetists regarding the complications expected in the case. In case of ICA bleed, the target should be to achieve a temporary hemostasis. In small tears, cottonoids for pressure and bipolar for cauterization will help stop the bleeding, while in larger tears, giving moderate pressure using crushed muscle and cottonoids to achieve intra-operative hemostasis should be tried. After intraoperative hemostasis, the patient needs to be shifted to angiography suite for endovascular stent placement.